Critical Crossroads: Coastline Challenges in Preserving Maine's Working Waterfronts - Coombs, Monique (Maine Policy Review, 2023)
This commentary explores the challenges of sustaining Maine's working waterfronts, a complex issue shaped by rapid technological advancements, demographic shifts, and the delicate balance between preserving tradition and adapting to new trends. The author discusses the impact of shared spaces on community life, particularly the waterfront, and how recent changes like COVID migration, climate-induced shifts, and remote work are reshaping Maine's coastal dynamics. The Maine Coast Fishermen's Association's efforts to address waterfront challenges through community conversations and resource guides are highlighted, showing how collaborations can foster understanding and shared values. The essay underscores the dynamic nature of safeguarding working waterfronts, reflecting on the intersection of resiliency, local business, shared spaces, and tradition in the ongoing struggle to find balance amidst changing coastal communities.
Keywords: working waterfront; coastal community; gentrification; covid migration; solastalgia; social inequity